Effect of age on antral follicle count, AMH levels and pregnancy outcomes in ART - Bhattacharya, Suparna; Dey, Satabdi; Yesireddy, Swapna; Chakraborty, Purba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: The purpose of this study is to determine if baseline antral follicle assessment and serum AMH level may serve additional information in predicting pregnancy outcome in in-vitro fertilization outcome in women of different age groups. Methods: A total of 680 cycles of in-vitro fertilization (IVF) in all clinics of Nova IVF fertility all over India from June 2023 to December 2024 were retrospectively analyzed in a cohort study. All the patients recruited in the study will be divided into 2 groups, based on age as-Group 1) Age<35 years (n=335) Group 2) Age>35 years (n=345). Each group will be further subdivided into 3 subgroups, depending upon their AMH (anti mullerian hormone) and AFC (antral follicle count). They were divided into very low AMH group, low-AMH group and high-AMH group. Similarly AFC groups were divided into <5, 5-9 and >10. Primary outcomes included the No of oocytes retrieved, No of mature oocytes, Biochemical Pregnancy rate, Clinical Pregnancy Rate. Secondary outcomes included fertilisation rate, blastulation rate, miscarriage rate. Results: The pregnancy rates for women below 35 years and above 35 years were not significant in the AMH subgroups but was significant in the AFC subgroup of 5-9, where it was 53.12% and 27.91% respectively. The Area Under the Curve (AUC) for the logistic regression model 0.656, indicating moderate discriminative ability. The distribution of AFC and AMH values by age group illustrates that younger women more frequently fall into higher AFC and AMH categories, supporting their use as age-related biomarkers. However, pregnancy and miscarriage rates are stratified by AMH and AFC groups failed to reach statistical significance, implying limited predictive value for these markers in isolation when it comes to final pregnancy outcome. Conclusions: Correlation analysis further affirmed that AFC has stronger associations with ovarian and embryological parameters compared to AMH. This aligns with prior research and clinical understanding, which recognizes AFC as a more dynamic and reliable predictor of ovarian reserve and treatment responsiveness. AMH, while useful, showed only moderate correlation with oocyte quantity and did not significantly predict fertilization, blastulation or pregnancy outcomes.